Technical and economic analysis of the use of biological insecticide Beauveria bassiana for the coffee berry borer control (Hypothenemus hampei) - Marcomini, Gilson Rogério (Revista Hipótese, 2015)
This study examined the use of the biological insecticide Beauveria bassiana (Bals.) in combating the coffee berry borer. The study was done in the years 2011/2012, 2012/2013 and 2013/2014. By the analysis of the results it can be seen that the use of biological management, provided better financial results to producers, which had a gain of R 15 to R 25 per sack. Furthermore, there is greater care with the natural environment, and also do not bring risk to human and animal health.